Low-warpage PP glass fiber reinforced material as well as preparation method and application thereof
By covering boron nitride on the surface of the glass fiber and reasonably matching fibers and microsphere expansion agents, the problem of shrinkage and warping of PP materials during the molding process is solved, and PP glass fiber reinforced materials with low warping and high mechanical properties are achieved , broaden its applications in the field of high performance requirements.
Patent Information
- Application Number
- CN202411695110.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-02-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing PP materials are prone to shrinkage and warping during the molding process, resulting in inconsistent product size, affecting the performance and appearance quality of use, and making it difficult to meet the high-performance requirements.
By coating boron nitride (BN) on the glass fiber surface, an efficient thermal conductivity network is built to improve the overall thermal conductivity of the composite material, uniformize the temperature distribution, reduce residual stress, and reduce the risk of warpage. At the same time, the modified glass fiber, ordinary glass fiber and microsphere expansion agent are reasonably matched to optimize the material composition to improve mechanical properties and dimensional stability.
It significantly reduces the shrinkage rate and warpage risk of PP materials, improves the mechanical properties and dimensional stability of the materials, and meets the needs of high-performance applications.
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of fiber composite materials, and in particular to a low-warpage PP glass fiber reinforced material and a preparation method and application thereof. Background Art
[0002] Polypropylene (PP) is one of the five most common general-purpose plastics. It has excellent chemical stability, electrical insulation and bending fatigue resistance, and its products have good surface gloss and are non-toxic. Therefore, it is widely used in industries such as home appliances, construction pipes and automobiles. However, PP also has disadvantages such as low strength and toughness, large molding shrinkage and poor creep resistance. During the molding process, the large shrinkage rate of PP causes excessive shrinkage of the product size. At the same time, affected by the processing conditions, the product shrinks unevenly, the dimensional consistency is difficult to ensure, and warping and deformation are prone to occur. Warping is a common quality defect of plastic products, which affects the performance and appearance quality of the products and limits their application in fields with higher requirements.
[0003] In order to expand the application scope of PP and improve its mechanical properties and dimensional stability, inorganic fillers are often used to modify PP, such as talc, calcium carbonate, kaolin and mica powder. In addition, fiber reinforcement is also an effective means to improve the performance of PP. Among them, glass fiber (GF) has become one of the commonly used reinforcement materials for PP due to its high specific strength, dimensional stability, heat resistance and creep resistance. However, although the addition of glass fiber can reduce the shrinkage rate of PP to a certain extent, it is still difficult to meet the needs of products with higher requirements for shrinkage rate and warpage performance.
[0004] Therefore, it is still necessary to develop glass fiber reinforced PP composite materials with low warpage and high mechanical properties to broaden the application of PP in fields with high performance requirements. Summary of the invention
[0005] The present invention aims to solve at least one of the technical problems existing in the prior art. To this end, the present invention provides a low-warpage PP glass fiber reinforced material, which has low shrinkage and excellent mechanical properties.
[0006] The present invention also provides a method for preparing the low-warpage PP glass fiber reinforced material.
[0007] The present invention also provides application of the low-warpage PP glass fiber reinforced material.
[0008] Specifically, the first embodiment of the present invention relates to a low-warpage PP glass fiber reinforced material, comprising the following raw materials in parts by mass:
[0009] PP60-70 parts;
[0010] 10-20 parts of modified glass fiber;
[0011] Ordinary glass fiber A10-20 parts;
[0012] 5-10 parts of microsphere expansion agent;
[0013] The modified glass fiber includes ordinary glass fiber B and BN coated on the surface of the ordinary glass fiber B.
[0014] PP is prone to shrinkage and warping during the molding process, which is related to the uneven temperature field and uneven shrinkage during the material cooling process. The uneven temperature field is due to the poor thermal conductivity of the PP matrix. The cooling rates of different parts during the molding and cooling process are different, resulting in a large temperature gradient inside the material, causing differences in shrinkage rates in different parts. Uneven temperature distribution in the mold, especially in areas where the product is thicker or cools more slowly, is prone to residual stress, causing warping deformation after molding. Uneven shrinkage refers to the fact that PP itself has a large shrinkage rate, which makes it more prone to uneven shrinkage during the cooling process.
[0015] In the prior art, common methods to reduce the warpage of PP products include optimizing mold design and cooling pipes to improve the temperature field distribution inside the mold. However, such methods mainly rely on external regulation and ignore the temperature field inside the material, making it difficult to fundamentally solve the warpage problem caused by insufficient thermal conductivity of the PP matrix. In addition, although the mechanical properties of PP can be improved and shrinkage can be reduced to a certain extent by adding inorganic fillers and other reinforcement methods, the thermal conductivity of the material itself has not been effectively improved, so the warpage problem still exists.
[0016] The present invention improves the overall thermal conductivity of the composite material by coating boron nitride (BN) on the surface of the glass fiber, making the temperature distribution of the product more uniform during the cooling process, reducing the residual stress caused by uneven cooling, and significantly reducing the risk of warping. BN is coated on the surface of the glass fiber, and the glass fiber is used as a carrier to construct an efficient thermal conductive network, which maximizes the advantages of boron nitride in improving thermal conductivity, thereby significantly reducing the shrinkage rate of the material. At the same time, under the same conditions, the amount of boron nitride added can be reduced to reduce the adverse effects on mechanical properties. Compared with traditional PP materials, this solution improves the cooling uniformity from the inside of the material, solves the problem of temperature field control that is difficult to achieve through mold optimization in the prior art, and can ensure the mechanical properties of the material.
[0017] Modified glass fiber is mixed with ordinary glass fiber, and the modified glass fiber is used to improve the thermal conductivity of the material without excessively sacrificing the mechanical properties of the material, thereby better balancing shrinkage rate and mechanical properties.
[0018] The microsphere expansion agent expands when heated during the molding process, offsetting some of the shrinkage of the material, thereby further reducing the overall shrinkage of the product. The microsphere expansion agent works synergistically with the two glass fibers to effectively improve the dimensional stability of the product and reduce the warping deformation caused by uneven shrinkage.
[0019] Through the reasonable combination of the above components, the low-warpage PP glass fiber reinforced material of the present invention not only has excellent mechanical properties and dimensional stability, but also significantly reduces the warpage generated during the molding process, providing an effective solution for the high-performance application of PP materials.
[0020] According to some embodiments of the present invention, the common glass fiber A has a diameter of 10 to 20 μm and a length of 10 to 20 mm. A certain aspect ratio helps to build a reinforcement network and improve the mechanical properties of the material.
[0021] According to some embodiments of the present invention, the common glass fiber A is alkali-free glass fiber (E glass fiber). E glass fiber has excellent mechanical properties, corrosion resistance and electrical insulation, and can better balance cost and material performance.
[0022] According to some embodiments of the present invention, the mass ratio of the modified glass fiber to the ordinary glass fiber A is 2:1 to 1:1, for example, 2:1, 1.5:1 or 1:1.
[0023] According to some embodiments of the present invention, the modified glass fiber is 15 to 20 parts by mass, for example, it can be 15 parts by mass, 16 parts by mass, 17 parts by mass, 18 parts by mass, 19 parts by mass or 20 parts by mass; the ordinary glass fiber A is 10 to 15 parts by mass, for example, it can be 10 parts by mass, 11 parts by mass, 12 parts by mass, 13 parts by mass, 14 parts by mass or 15 parts by mass.
[0024] According to some embodiments of the present invention, the modified glass fiber and / or the ordinary glass fiber A is / are treated with a coupling agent to improve its interface compatibility with the PP matrix.
[0025] According to some embodiments of the present invention, the coupling agent modification treatment includes: immersing the modified glass fiber and / or ordinary glass fiber A in a coupling agent solution, filtering out, and drying.
[0026] The coupling agent for modification includes but is not limited to KH550, KH560, KH570, etc. The mass concentration of the coupling agent solution can be in the range of 0.5% to 2%, and the soaking time can be selected according to the actual situation, for example, between 0.5 and 4 hours, and the volume of the soaking liquid is selected to be a suitable volume sufficient to completely cover the fiber. The present invention does not impose strict restrictions on the raw materials and process parameters for modification, and can be reasonably adjusted according to actual needs and experience.
[0027] According to some embodiments of the present invention, the method for preparing the modified glass fiber comprises:
[0028] S1, adding ordinary glass fiber B into dopamine solution and immersing it, taking the solid phase to obtain dopamine modified glass fiber;
[0029] S2. Mixing dopamine-modified glass fiber and BN in a dispersed phase, filtering, and drying to obtain modified glass fiber.
[0030] Pre-modification of the glass fiber with dopamine can enhance the interfacial interaction between the glass fiber and boron nitride, promote the uniform coating of BN on the surface of the glass fiber, and then build an efficient thermal conductive network, maximize the advantages of BN in improving thermal conductivity, and further enhance the mechanical properties and dimensional stability of the material.
[0031] According to some embodiments of the present invention, the method further comprises the step of subjecting the modified glass fiber to a coupling agent modification treatment.
[0032] According to some embodiments of the present invention, the added amount of BN is 5% to 20% of the mass of the ordinary glass fiber B, for example, it can be 5%, 10%, 12%, 15%, 18% or 20%.
[0033] According to some embodiments of the present invention, the added amount of BN is 10% to 15% of the mass of the ordinary glass fiber B. Controlling the added amount of BN helps to balance the mechanical properties and thermal conductivity of the material.
[0034] According to some embodiments of the present invention, the particle size of the BN is 200-500 nm, for example, 200-300 nm. Nano-scale particles have a larger specific surface area, which is conducive to BN coating on the surface of glass fiber and improving the mechanical properties of the material.
[0035] According to some embodiments of the present invention, the concentration of the dopamine solution is 1 to 5 g / L, for example, 1 g / L, 2 g / L, 3 g / L, 4 g / L or 5 g / L.
[0036] According to some embodiments of the present invention, the pH of the dopamine solution is 8 to 9. Specifically, to prepare the dopamine solution, the pH of the solution can be adjusted to 8 to 9 by adding Tris buffer. Under weak alkaline conditions, dopamine is self-polymerized to form a uniform polydopamine layer, which provides favorable conditions for subsequent BN coating.
[0037] According to some embodiments of the present invention, the mass ratio of dopamine in the dopamine solution to ordinary glass fiber B is 1:5-10, for example, specifically 1:5, 1:6, 1:7, 1:8, 1:9 or 1:10.
[0038] According to some embodiments of the present invention, stirring is performed during the impregnation process. The present invention does not impose any specific limitation on the stirring rate, which can be selected based on conventional experience.
[0039] According to some embodiments of the present invention, the immersion time is not less than 15 hours, for example, it can be 15 hours, 20 hours or 24 hours.
[0040] According to some embodiments of the present invention, in step S1, filtering and drying are performed after the impregnation to obtain a solid phase.
[0041] According to some embodiments of the present invention, in step S2, ultrasonic treatment is performed during the mixing process to improve the dispersibility of BN and facilitate BN coating on the surface of the glass fiber.
[0042] According to some embodiments of the present invention, the ultrasonic treatment time is 30 to 60 min, for example, 30 min, 40 min, 50 min or 60 min.
[0043] The present invention does not impose any specific restrictions on the ultrasonic treatment parameters, which can be selected according to conventional experience, for example, the ultrasonic treatment frequency is 20 to 40 kHz, and the power is 100 to 500 W. During the ultrasonic process, the solution temperature may rise, and a water bath can be used to control the temperature near room temperature to ensure the stability of the solution.
[0044] According to some embodiments of the present invention, in step S2, the dispersed phase includes water.
[0045] According to some embodiments of the present invention, in step S2, the dispersed phase includes water and a dispersant. Adding a dispersant can improve the dispersibility of BN in the solution.
[0046] According to some embodiments of the present invention, the dispersant includes at least one of sodium lauryl sulfate and polyvinyl alcohol.
[0047] According to some embodiments of the present invention, the added amount of the dispersant is 1% to 5% by mass of the BN, for example, 1%, 2%, 3%, 4% or 5%.
[0048] According to some embodiments of the present invention, the liquid-to-solid ratio of the dispersed phase to the dopamine-modified glass fiber is 20-50 mL / g, for example, 20 mL / g, 30 mL / g, 40 mL / g or 50 mL / g.
[0049] According to some embodiments of the present invention, stirring is performed during the mixing process. The present invention does not impose any specific limitation on the stirring rate, which can be selected based on conventional experience.
[0050] The present invention does not impose any restrictive regulations on the type of the common glass fiber B in the modified glass fiber, and the type of the common glass fiber A can be referred to for selection.
[0051] According to some embodiments of the present invention, an antioxidant is also included. The type and amount of the antioxidant can be selected according to actual needs and experience, and are not subject to specific restrictions. Commonly used antioxidants include antioxidant 1010 (pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate). The amount of the antioxidant added can be controlled at 0.2% to 0.5% of the mass of PP, for example, 0.2%, 0.3%, 0.4% or 0.5%.
[0052] According to some embodiments of the present invention, the foaming temperature of the microsphere expansion agent is 180-200° C. The microsphere expansion agent can be purchased commercially, and a microsphere expansion agent with a comparable foaming temperature is selected according to the molding temperature of PP.
[0053] A second embodiment of the present invention relates to a method for preparing the low-warpage PP glass fiber reinforced material, comprising the following steps:
[0054] The raw materials except the modified glass fiber and the ordinary glass fiber A are milled, and the modified glass fiber and the ordinary glass fiber A are added and mixed to obtain the PP / glass fiber prepreg; wherein the milling and mixing temperatures are lower than the foaming temperature of the microsphere expansion agent.
[0055] The open milling process can achieve efficient material preparation and is conducive to industrial large-scale production. During the mixing process, the shear force can be controlled by adjusting the roller distance, thereby effectively reducing the breakage of the glass fiber, protecting the integrity of the fiber, and ensuring the mechanical properties of the product.
[0056] The temperature of the opening and mixing is set below the foaming temperature of the microsphere expansion agent, which avoids the premature expansion of the microsphere expansion agent and ensures the stability of the material during the processing.
[0057] According to some embodiments of the present invention, the temperature of the open rolling and / or mixing is 155-170°C, for example, specifically 155°C, 160°C, 165°C or 170°C.
[0058] According to some embodiments of the present invention, the roller spacing of the open mill is 1 to 2 mm, for example, specifically 1 mm, 1.5 mm or 2 mm.
[0059] According to some embodiments of the present invention, the mixing roller distance is 3 to 6 mm, for example, it can be 3 mm, 3.5 mm, 4 mm, 4.5 mm, 5 mm, 5.5 mm or 6 mm.
[0060] Before adding glass fiber, adjust the roller distance to a smaller distance to fully mix other materials. After adding glass fiber, appropriately increase the roller distance to reduce shear force and reduce the breakage or damage of glass fiber. In actual operation, when the roller distance is too large, you can regularly use a scraper tool to push the material from both sides to the middle to better ensure the uniformity of the overall mixing.
[0061] The present invention does not impose any restrictive regulations on the time of opening and mixing, and can be selected according to actual experience. Under the premise of ensuring that the materials are mixed evenly, the processing time is shortened as much as possible to reduce oxidation.
[0062] According to some embodiments of the present invention, the step of compression molding the PP / glass fiber prepreg is also included. The compression molding temperature can be controlled near the foaming temperature of the microsphere expansion agent, so that the expansion agent can expand moderately during the molding process, offset part of the material shrinkage, effectively reduce the shrinkage rate of the product, and reduce the warping deformation problem after molding.
[0063] According to some embodiments of the present invention, the temperature of the compression molding is not lower than the foaming temperature of the microsphere expansion agent.
[0064] According to some embodiments of the present invention, the temperature of the compression molding is 180-200°C, the pressing time is 10-20 min, and the pressing pressure is 1-3 MPa. Specifically, the temperature of the compression molding can be 180°C, 185°C, 190°C, 195°C or 200°C, the pressing time can be 10 min, 15 min or 20 min, and the pressing pressure can be 1 MPa, 1.5 MPa, 2 MPa, 2.5 MPa or 3 MPa.
[0065] According to some embodiments of the present invention, preheating is also included before the compression molding to allow the mold temperature to reach a constant temperature state.
[0066] According to some embodiments of the present invention, the method further comprises performing pressure holding and / or pressure cooling after the compression molding.
[0067] A third aspect of the present invention relates to the use of the aforementioned low-warpage PP glass fiber reinforced material in automobiles or household appliances.
[0068] Low-warpage PP glass fiber reinforced materials have excellent dimensional stability and mechanical properties, and show significant advantages in automotive and home appliance applications: In the automotive field, they can be used for door panels, bumpers, center consoles, etc., and their excellent dimensional stability helps to ensure assembly quality and safety in use. In the field of home appliances, they can be used as decorative parts such as shells, which improves the durability and service life of home appliance products.
[0069] In this article, the microsphere expansion agent is an additive with the property of thermal expansion, including a polymer shell and a low-boiling point liquid core. The low-boiling point liquid wrapped inside the microsphere is heated and vaporized, so that the volume of the microsphere expands to form a closed-cell foaming structure. The commercially available microsphere expansion agent is represented by the expandable microspheres produced by Matsumoto Oil Pharmaceutical Co., Ltd. of Japan.
[0070] Herein, the numerical ranges involved include the endpoint values and cover any sub-ranges within the range, such as the ranges obtained by any combination of the specifically listed values. In addition, "above" or "below" includes the values themselves.
[0071] Unless otherwise specified, size parameters such as diameter, length, particle size, etc. refer to average values.
[0072] Other features and advantages of the present invention will be set forth in the description which follows, and in part will be apparent from the description, or may be learned by practice of the present invention. DETAILED DESCRIPTION
[0073] The embodiments of the present invention are described in detail below. The embodiments described below are exemplary and are only used to explain the present invention, and should not be construed as limiting the present invention.
[0074] In the following examples, some of the raw materials are described as follows:
[0075] PP: ExxonMobil, 4712E1.
[0076] Microsphere expansion agent: produced by Matsumoto Oil Pharmaceutical Co., Ltd., Japan, foaming temperature 180℃.
[0077] Boron nitride, particle size 200nm.
[0078] Long glass fiber (LGF), diameter 13 μm, length 15 mm.
[0079] Unless otherwise specified, the raw materials or equipment involved are commercially available conventional products.
[0080] Example 1
[0081] A low-warpage glass fiber reinforced PP material was prepared, comprising the following steps:
[0082] 1. Prepare 2 g / L dopamine solution, adjust its pH to 8.5 with Tris buffer, add LGF and dopamine solution into a three-necked flask (the mass ratio of LGF to dopamine is 8:1), stir magnetically at room temperature for 24 h, and finally filter and dry to obtain dopamine-modified glass fiber (LGF-DA).
[0083] 2. Add BN, LGF-DA and polyvinyl alcohol solution into a three-necked flask (the liquid-to-solid ratio of polyvinyl alcohol solution and LGF-DA is 40 mL / g; BN is 12% of the mass of LGF; the mass of polyvinyl alcohol is 3% of the mass of BN), stir for 40 minutes under ultrasound (frequency 30 kHz, power 300 W), and finally filter and dry to obtain boron nitride-modified glass fiber LGF-BN for later use.
[0084] 3. Soak LGF-BN and LGF in a dilute aqueous solution of coupling agent KH550 (concentration 1.5%) for 2 hours, take them out and place them in a 100°C oven to dry for later use.
[0085] 4. Preparation of PP / LGF / LGF-BN composite materials by open refining-compression molding method:
[0086] 4.1. Adjust the roller gap to 1.5 mm. When the temperature of the double rollers rises to 160±5°C, add PP60 (mass part), microsphere expansion agent (10 mass parts), and antioxidant (1010) (0.3 mass parts) to melt through the roller gap.
[0087] 4.2. Adjust the roller distance to 4.5 mm, add 15 parts by weight of coupling agent modified LGF and coupling agent modified LGF-BN, mix for 15 min, and sheet to obtain PP / LGF / LGF-BN composite prepreg;
[0088] 4.3. Cut the cooled PP / LGF / LGF-BN composite prepreg into the required shape, stack them in multiple layers, and then place them in a hot press for compression molding, wherein the temperature is 180°C, the pressure is 2MPa, the preheating time is 10min, the holding time is 10min, and the pressure is cooled.
[0089] Example 2
[0090] A low-warpage glass fiber reinforced PP material was prepared, comprising the following steps:
[0091] 1. Prepare 3 g / L dopamine solution, adjust its pH to 8.5 with Tris buffer, add LGF and dopamine solution into a three-necked flask (the mass ratio of LGF to dopamine is 8:1), stir magnetically at room temperature for 20 h, and finally filter and dry to obtain dopamine-modified glass fiber (LGF-DA).
[0092] 2. Add BN, LGF-DA and polyvinyl alcohol solution into a three-necked flask (liquid-to-solid ratio of polyvinyl alcohol solution and LGF-DA is 50 mL / g; BN is 12% of the mass of LGF; the mass of polyvinyl alcohol is 5% of the mass of BN), stir for 30 minutes under ultrasound (frequency 30 kHz, power 300 W), and finally filter and dry to obtain boron nitride modified glass fiber LGF-BN for later use.
[0093] 3. Soak LGF-BN and LGF in a dilute aqueous solution of coupling agent KH550 (concentration 1.5%) for 2 hours, take them out and place them in a 100°C oven to dry for later use.
[0094] 4. Preparation of PP / LGF / LGF-BN composite materials by open refining-compression molding method:
[0095] 4.1. Adjust the roller gap to 1.5 mm. When the temperature of the double rollers rises to 160±5°C, add PP60 (mass part), microsphere expansion agent (10 mass parts), and antioxidant (1010) (0.3 mass parts) to melt through the roller gap.
[0096] 4.2. Adjust the roller distance to 4.5 mm, add 10 parts by weight of coupling agent-modified LGF and 20 parts by weight of coupling agent-modified LGF-BN, mix for 15 min, and sheet to obtain PP / LGF / LGF-BN composite prepreg;
[0097] 4.3. Cut the cooled PP / LGF / LGF-BN composite prepreg into the required shape, stack them in multiple layers, and then place them in a hot press for compression molding, wherein the temperature is 180°C, the pressure is 2MPa, the preheating time is 10min, the holding time is 10min, and the pressure is cooled.
[0098] Example 3
[0099] A low-warpage glass fiber reinforced PP material was prepared, comprising the following steps:
[0100] 1. Prepare 2 g / L dopamine solution, adjust its pH to 8.5 with Tris buffer, add LGF and dopamine solution into a three-necked flask (the mass ratio of LGF to dopamine is 8:1), stir magnetically at room temperature for 24 h, and finally filter and dry to obtain dopamine-modified glass fiber (LGF-DA).
[0101] 2. Add BN, LGF-DA and polyvinyl alcohol solution into a three-necked flask (the liquid-to-solid ratio of polyvinyl alcohol solution and LGF-DA is 40 mL / g; BN is 12% of the mass of LGF; the mass of polyvinyl alcohol is 3% of the mass of BN), stir for 40 minutes under ultrasound (frequency 30 kHz, power 300 W), and finally filter and dry to obtain boron nitride-modified glass fiber LGF-BN for later use.
[0102] 3. Soak LGF-BN and LGF in a dilute aqueous solution of coupling agent KH550 (concentration 1.5%) for 2 hours, take them out and place them in a 100°C oven to dry for later use.
[0103] 4. Preparation of PP / LGF / LGF-BN composite materials by open refining-compression molding method:
[0104] 4.1. Adjust the roller gap to 1.5 mm. When the temperature of the double rollers rises to 160±5°C, add PP60 (part by weight), microsphere expansion agent (5 parts by weight), and antioxidant (1010) (0.3 parts by weight) to melt through the roller gap.
[0105] 4.2. Adjust the roller distance to 4.5 mm, add 15 parts by weight of coupling agent modified LGF and coupling agent modified LGF-BN, mix for 15 min, and sheet to obtain PP / LGF / LGF-BN composite prepreg;
[0106] 4.3. Cut the cooled PP / LGF / LGF-BN composite prepreg into the required shape, stack them in multiple layers, and then place them in a hot press for compression molding, wherein the temperature is 180°C, the pressure is 2MPa, the preheating time is 10min, the holding time is 10min, and the pressure is cooled.
[0107] Comparative Example 1
[0108] A glass fiber reinforced PP material was prepared, comprising the following steps:
[0109] 1. Soak LGF in a dilute aqueous solution of coupling agent KH550 (concentration 1.5%) for 2 hours, take it out and place it in a 100°C oven to dry for use.
[0110] 2. Preparation of PP / LGF composite materials by open refining-compression molding method:
[0111] 2.1. Adjust the roller gap to 1.5 mm. When the temperature of the double rollers rises to 160±5°C, add PP60 by mass, 10 by mass of microsphere expansion agent, and 0.3 by mass of antioxidant (1010) to melt through the roller gap;
[0112] 2.2. Adjust the roller distance to 4.5 mm, add 30 parts by weight of coupling agent-modified LGF, mix for 15 min, and sheet to obtain PP / LGF composite prepreg;
[0113] 2.3. Cut the cooled PP / LGF composite prepreg into the required shape, stack them in multiple layers, and then place them in a hot press for compression molding, wherein the temperature is 180°C, the pressure is 2MPa, the preheating time is 10min, the holding time is 10min, and the pressure is cooled under pressure.
[0114] Comparative Example 2
[0115] PP material is prepared by open refining-compression molding method:
[0116] 1. Adjust the roller gap to 1.5 mm. When the temperature of the double rollers rises to 160±5°C, add PP60 by mass and 0.3 by mass of antioxidant (1010) to melt through the roller gap;
[0117] 2. Adjust the roller distance to 2mm, mix for 15min, and then sheet to obtain PP sheet;
[0118] 3. Cut the cooled PP sheet into the required shape, stack it in multiple layers, and then place it in a hot press for compression molding, where the temperature is 180°C, the pressure is 2MPa, the preheating time is 10min, the holding time is 10min, and the pressure is cooled under pressure.
[0119] Test Case
[0120] The material properties of Examples 1 to 3 and Comparative Examples 1 to 2 were tested. Test pieces were prepared according to the relevant test standards and corresponding processes. The test results are shown in Table 1.
[0121] Tensile strength: GB / T1447-2005.
[0122] Flexural strength, flexural modulus: GB / T1449-2005.
[0123] Notched impact strength: GB / T1451-2005.
[0124] Shrinkage rate: (corresponding size of mold - corresponding size after molding) * 100% / corresponding size of mold.
[0125] The formula comparison and performance data of Examples 1 to 3 and Comparative Examples 1 to 2 are shown in Table 1.
[0126] Table 1
[0127] Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 PP / weight 60 60 60 60 60 Modified LGF-BN / mass parts 15 20 15 -- -- Modified LGF / mass 15 10 15 30 -- Microsphere expansion agent / mass 10 10 5 10 -- Antioxidant / mass 0.3 0.3 0.3 0.3 0.3 Tensile strength / MPa 115.5 107.2 122.9 118.5 32 Bending strength / MPa 132.3 123.5 140.3 146.4 45 <![CDATA[Notch impact strength / kJ.m -2 > 26.4 25.2 27.1 27.8 2.5 Transverse shrinkage / % 0.72 0.70 0.8 0.87 1.4 Longitudinal shrinkage / % 0.73 0.71 0.81 0.89 1.6
[0128] The above results show that the material of the embodiment has excellent overall performance in mechanical properties and shrinkage rate, etc. On the premise that the mechanical properties meet the requirements, the shrinkage rate of the material can be effectively reduced and the dimensional stability can be further improved by appropriately increasing the amount of microsphere expansion agent or modified LGF-BN.
[0129] In Comparative Example 1, no modified LGF-BN was added, and the shrinkage rate increased significantly, indicating that modified LGF could not effectively control the shrinkage of the material. In contrast, modified LGF is more conducive to the improvement of mechanical properties, but when the proportion of modified LGF is too high, the improvement of mechanical properties tends to be flat. Therefore, a reasonable combination of modified LGF and modified LGF-BN can give full play to the reinforcing effect of glass fiber while significantly improving the dimensional stability of the material. In Comparative Example 2, no glass fiber and microsphere expansion agent were added, and the mechanical properties and shrinkage rate of the material were very poor.
[0130] The above results show that the material of the embodiment shows significant advantages in reducing shrinkage and improving mechanical properties by rationally combining modified glass fiber, ordinary glass fiber and microsphere expansion agent. Based on this performance advantage, the material is very suitable for application in the automotive and home appliance fields, and can significantly improve the dimensional stability and durability of the product, better meeting the actual application needs.
[0131] The embodiments of the present invention are described in detail above, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge scope of ordinary technicians in the relevant technical field without departing from the purpose of the present invention.
Claims
1. A low warpage PP glass fiber reinforced material, characterized by: The preparation comprises the following raw materials in parts by mass: PP60-70 parts; 10-20 parts of modified glass fiber; Ordinary glass fiber A10-20 parts; 5-10 parts of microsphere expansion agent; The modified glass fiber includes ordinary glass fiber B and BN coated on the surface of the ordinary glass fiber B.
2. The low warpage PP glass fiber reinforced material according to claim 1, characterized in that: The diameter of the ordinary glass fiber A is 10 to 20 μm, and the length is 10 to 20 mm; and / or the ordinary glass fiber A is an alkali-free glass fiber; and / or the diameter of the ordinary glass fiber B is 10 to 20 μm, and the length is 10 to 20 mm; and / or the ordinary glass fiber B is an alkali-free glass fiber; and / or the mass ratio of the modified glass fiber to the ordinary glass fiber A is 2:1 to 1:
1.
3. The low warpage PP glass fiber reinforced material according to claim 1 or 2, characterized in that: The preparation method of the modified glass fiber comprises: S1, adding ordinary glass fiber B into dopamine solution and immersing it, taking the solid phase to obtain dopamine modified glass fiber; S2. Mixing dopamine-modified glass fiber and BN in a dispersed phase, filtering, and drying to obtain modified glass fiber.
4. The low warpage PP glass fiber reinforced material according to claim 3, characterized in that: The concentration of the dopamine solution is 1-5 g / L; and / or, the pH of the dopamine solution is 8-9; and / or, the mass ratio of dopamine in the dopamine solution to ordinary glass fiber B is 1:5-10; and / or, the immersion time is not less than 15 hours; and / or, in step S2, ultrasonic treatment is performed during the mixing process; and / or, the dispersed phase includes water.
5. The low warpage PP glass fiber reinforced material according to claim 4, characterized in that: In step S2, the dispersed phase includes water and a dispersant; Optionally, the dispersant includes at least one of sodium lauryl sulfate and polyvinyl alcohol; Optionally, the amount of the dispersant added is 1% to 5% of the mass of the BN; Optionally, the liquid-solid ratio of the dispersed phase to the dopamine-modified glass fiber is 20 to 50 mL / g.
6. The low warpage PP glass fiber reinforced material according to claim 1 or 3, characterized in that: The added amount of the BN is 5% to 20% of the mass of the ordinary glass fiber B; and / or the average particle size of the BN is 200 to 500 nm.
7. The low warpage PP glass fiber reinforced material according to claim 1, characterized in that: It also includes an antioxidant; and / or the modified glass fiber and / or the ordinary glass fiber A is treated with a coupling agent for modification.
8. The method for preparing a low-warpage PP glass fiber reinforced material according to any one of claims 1 to 7, characterized in that: The following steps are involved: The raw materials except the modified glass fiber and the ordinary glass fiber A are milled, and the modified glass fiber and the ordinary glass fiber A are added and mixed to obtain the PP / glass fiber prepreg; wherein the milling and mixing temperatures are lower than the foaming temperature of the microsphere expansion agent.
9. The preparation method according to claim 8, characterized in that: The temperature of the open milling and / or mixing is 155-170° C.; and / or, the roller distance of the open milling is 1-2 mm; and / or, the roller distance of the mixing is 3-6 mm; and / or, it also includes the step of: compression molding the PP / glass fiber prepreg, and the compression molding temperature is not lower than the foaming temperature of the microsphere expansion agent.
10. Use of the low-warpage PP glass fiber reinforced material according to any one of claims 1 to 7 in automobiles or household appliances.
Citation Information
Patent Citations
Polypropylene composite material with high heat conductivity
CN107868337A
Polypropylene material suitable for manufacturing automobile interior decorations, preparation method and use thereof
CN109851923A